(untitled) (Revista Electrónica Calidad en la Educación Superior, 2024)
Public higher education institutions have social, academic, and financial challenges that test their work. Additionally, the growing number of academic programs has increased the demand for verified quality among the population. In this context, international rankings, and national or international accreditations become crucial for certifying the education of competent professionals capable of facing the challenges of the modern labor market. As a result, the Escuela de Ingeniería Topográfica (EIT) initiated a self-assessment process in 2011 to identify the strengths, opportunities, weaknesses, and threats of the program, providing the necessary inputs for its improvement. This article summarizes the main findings, achievements, and difficulties experienced throughout the different self-assessment processes of the Topographical Engineering program, using the methodology proposed by Jara (2018) for systematizing experiences. In conclusion, the EIT has learned valuable lessons from these processes, highlighting the importance of self-assessment and continuous improvement, which has strengthened the academic program and adapted the educational offer to current demands.